Behavioral Dynamics of Smart Home Adoption: A PLS-SEM Study in Emerging Markets - Bora Ly; Romny Ly; Sokhom Ma (Human Behavior and Emerging Technologies)
This study investigates the adoption of smart home technologies (SHTs) in Cambodia by integrating the unified theory of acceptance and use of technology (UTAUT) and diffusion of innovation (DOI) theories, a novel approach in an emerging market context. Focusing on effort expectancy, social influence, and facilitating conditions such as infrastructure reliability and technological support, this study analyzes quantitative data from 379 Cambodian users using partial least squares structural equation modeling (PLS-SEM). The results indicate that effort expectancy significantly drives SHT adoption, aligning with UTAUT and DOI frameworks. Social influence and robust facilitating conditions are crucial for promoting SHT adoption. These findings imply that policymakers should enhance infrastructure and provide technological support, whereas businesses should leverage social networks to facilitate SHT integration. This study offers essential insights for designing effective technology adoption strategies in emerging markets by accounting for the local cultural and infrastructural dynamics.